Students’ Perception on the Effectiveness of Online Classes During Pandemic - Rijal, Deependra (The EFFORTS, Journal of Education and Research, 2022)
The present study aimed at finding out students' perception on the effectiveness of online classes conducted during the pandemic situation of COVID -19. It attempted to find the students' perceptions for effective classes. I applied cross sectional survey design. For this, survey questionnaires were prepared in google form. Those students who were taking online classes at Nilkantha Multiple Campus in bachelor and master levels and education, arts and commerce faculties were selected as respondents for my research through convenience sampling procedure. Students were requested to reply the questions posted in their Facebook group of each classes. The data were collected, analyzed and interpreted by the help pie-charts and diagrams and descriptions. The result of this study indicated that respondents were not satisfied with their online classes due to low participation, lack of enough interaction, unattractive content delivery and the problems of poor internet and frequent power cut. Even though online classes were reported to be convenient in term of saving time, still the students perceived it to be less effective.